(untitled) (IJOVTECH, 2026)
The paper discusses the perceptions of artificial intelligence (AI) among Ebonyi State students in Nigeria in a comparative manner. The study adopted a primary data collection technique in which structured questionnaires were used to survey 400 undergraduate students of Ebonyi State University in the stratified random sampling technique to represent the different genders, ages, and faculties. The study is framed by the Technology Acceptance Model and Diffusion of Innovations theory as the method of investigating the perceptions with references to the following variables: perceived benefits, fears, ethical issues, curriculum integration and job effects. Data was analyzed using descriptive statistics, t-tests, and ANOVA showing that there were significant gender-based differences with females perceiving AI as more useful towards learning than males and less terrifying. A significant difference was also observed in the faculties, with science students having more positive perceptions generally. The average scores on the 5-point Likert scale were between 3.5 and 3.7 which corresponded to moderate optimism with a certain degree of anxiety. The sample was demographically represented by 55 percent males and 45 percent females with most of the sample aged between 18-20 (41.25) and faculty of sciences (27%). Results obtained are consistent with world literature of mixed AI perceptions in the educational sphere, with special emphasis on contextual peculiarities of a developing state, such as Ebonyi State, which has limited access to AI tools. The research highlights that specific educational interventions are necessary to establish a perception gap and ensure that AI will be used equitably. One of the suggested recommendations is the adoption of AI literacy in curricula, as well as the training of non-technical faculties. The study is relevant in terms of comprehending the perceptions of AI in underexplored African settings in order to inform policymakers and educators to promote an inclusive technological development.